Root length is proxy for high-throughput screening of waterlogging tolerance in Urochloa spp. grasses - Jiménez, Juan de la Cruz; Cardoso, Juan Andrés; Kotula, Lukasz; Veneklaas, Erik Jan; Pedersen, Ole; Colmer, Timothy D. (Commonwealth Scientific and Industrial Research Organisation, 2021)
C4 perennial Urochloa spp. grasses are widely planted in extensive areas in the tropics. These areas are continuously facing waterlogging events, which limits plant growth and production. However, no commercial cultivar combining excellent waterlogging tolerance with superior biomass production and nutritional quality is available. The objective of this study was to identify root traits that can be used for selecting waterlogging tolerant species of Urochloa. Root respiration, root morphological, architectural and anatomical traits were evaluated in eight contrasting Urochloa spp. genotypes grown under aerated or deoxygenated stagnant solutions. Moreover, modelling of internal aeration was used to relate differences in root traits and root growth in waterlogged soils. Increased aerenchyma formation in roots, reduced stele area and development of a fully suberised exodermis are characteristics improving internal aeration of roots and therefore determining waterlogging tolerance in these C4 forage grasses. Waterlogging-tolerant genotypes had steeper root angles and greater root lengths than the waterlogging-sensitive genotypes. In stagnant conditions, waterlogging-tolerant genotypes had a greater proportion of aerenchyma and reduced stele area in root cross-sections, had deeper roots, steeper root angle and larger root biomass, which in turn, allowed for greater shoot biomass. Total root length had the strongest positive influence on shoot dry mass and can therefore be used as proxy for selecting waterlogging tolerant Urochloa genotypes.